2011
DOI: 10.1002/jid.1827
|View full text |Cite
|
Sign up to set email alerts
|

Poverty in Rural India: Variations in Factors Influencing Dynamics of Chronic Poverty

Abstract: The article studies the dynamics of chronic poverty in rural India. The article attempts to analyse the factors influencing the incidence and mobility of poverty and the changes in the influence of these factors over time. This article uses the household panel survey data collected by NCAER. It examines whether there has been change in the influence of factors such as village level infrastructure, household size and composition, and economic growth on poverty dynamics in different periods of time. The impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
1
16
0
1
Order By: Relevance
“…Escape rates for OBC households, 43%, fell between these two extremes. Dhamija and Bhide (2013) extended the analysis of the same NCAER data to 1998–99 and also found that both Dalits and Adivasis were less likely to escape poverty, although the coefficient estimating the log odds of escape for Adivasis, −1.18, was over twice that for Dalits, −0.56 (2013: 692).…”
Section: Background and Motivationmentioning
confidence: 85%
See 1 more Smart Citation
“…Escape rates for OBC households, 43%, fell between these two extremes. Dhamija and Bhide (2013) extended the analysis of the same NCAER data to 1998–99 and also found that both Dalits and Adivasis were less likely to escape poverty, although the coefficient estimating the log odds of escape for Adivasis, −1.18, was over twice that for Dalits, −0.56 (2013: 692).…”
Section: Background and Motivationmentioning
confidence: 85%
“…Bhide and Methta (2008) using the NCAER data found evidence for higher rates for Adivasis falling into severe poverty and for Dalits falling into moderate poverty. Dhamija and Bhide (2013), analyzing the same data in a multivariate model, found only non-significant caste differences after controlling for other household and area characteristics. The retrospective methods in smaller state-specific samples generally find higher descent rates for disadvantaged castes than for forward castes although the differences among the disadvantaged castes varies from one location to another.…”
Section: Background and Motivationmentioning
confidence: 95%
“…Irrigation coverage differed significantly in 2001, with non‐poor households having a substantially higher proportion of irrigation coverage (42.8 per cent), followed by households that had moved out of poverty (37.6 per cent). Irrigation is an important component of infrastructure that enhances returns to the endowment, specifically the land, thereby contributing to households’ movement out of poverty (Baulch and Hoddinott ; Dhamija and Bhide ). With improved irrigation access, even for poor households, irrigation coverage was not significantly different in 2007.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the importance of location specificity in the NLSS studies, we adopted the interpolated poverty line derived from the NLSS poverty lines. A similar method has been applied by other researchers to establish a poverty line (Dhamija and Bhide ; Haddad and Ahmed ; Radeny and Van den Berg ). Subsequently, the household poverty line was estimated based on a standardised household size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation